The Mathematical Modeling for a Study of Suction Heads of a Continuous Operation Thermal Water Pump with Steam System - สิตรานนท์, จิรวัฒน์ (Srinakharinwirot University Engineering Journal, 2020)
The objectives of this article was to study the suction heads of a thermal water pump with steam system. The system consisted of a steam tank, condenser tank and feed water tank. However, in this research we studied the suction head of 2 - 8 m for 10 hours per test. However, in this research we studied the suction head of 2 - 8 m for 10 hours per test and compare the different with the experiments of the water temperature in the steam tank, temperature in the condenser tank and pressure inside the condenser tank. From the study we found a long beginning operating time. However, for the next cycle, it might use less energy and had short operating time. When the suction head increased, the total pumped water volume was reduced. But on the contrary the pumping cycle time was increased. The number of pumping cycles then decreased. However, pumping efficiency increased with the suction heads increases. At 8 m head, we got 112 kJ potential energy stored, 1.86619% pump efficiency and 1,428 L pumped water and at the 2 m head: the potential energy stored was 40 kJ, the pump efficiency was 0.66649% and the pumped water was 2,040 L. In conclusion, increasing the suction head enhanced the pump efficiencies. From this research of the mathematical model were different from the measured values by 0.7145, 1.8714 and 8.3831% for the water temperature in the steam tank, temperature in the condenser tank and pressure inside the condenser tank.